2016
DOI: 10.1007/s10826-016-0450-5
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Parental Reflective Function in the Adjustment of Young Adults

Abstract: Reflective function is the capacity to reflect on one's own thoughts and feelings, and those of others. Parental reflective function has been found significant for children's social and emotional development. However, research has mostly been restricted to mothers and to early stages of development, and there is a paucity of observations on the effects of parental reflective function in later stages. The aim of the present study is to explore the significance of mothers' and fathers' reflective function for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
1
11
0
3
Order By: Relevance
“…This is unfortunate because adolescence is a developmental period marked by changes in parents' roles, by children's increased strivings for independence, and by changes in emotional arousal (Soenens, Vansteenkiste, & Beyers, 2019;Steinberg & Morris, 2001). As such, adolescence is a developmental stage in which parents' reflective abilities may be challenged and in which these abilities are at the same time particularly important for adolescents' social and emotional well-being and for the parentadolescent interaction (Benbassat & Shulman, 2016;Milan, Ramirez, & Carlone, 2017;Kobak, Abbott, Zisk, & Bounoua, 2017). By examining the role of parental reflective functioning among parents of adolescents, rather than among parents of young children, it becomes possible to include the adolescents' perception of parenting behavior.…”
Section: Parental Reflective Functioning and Parent-child Interactionmentioning
confidence: 99%
“…This is unfortunate because adolescence is a developmental period marked by changes in parents' roles, by children's increased strivings for independence, and by changes in emotional arousal (Soenens, Vansteenkiste, & Beyers, 2019;Steinberg & Morris, 2001). As such, adolescence is a developmental stage in which parents' reflective abilities may be challenged and in which these abilities are at the same time particularly important for adolescents' social and emotional well-being and for the parentadolescent interaction (Benbassat & Shulman, 2016;Milan, Ramirez, & Carlone, 2017;Kobak, Abbott, Zisk, & Bounoua, 2017). By examining the role of parental reflective functioning among parents of adolescents, rather than among parents of young children, it becomes possible to include the adolescents' perception of parenting behavior.…”
Section: Parental Reflective Functioning and Parent-child Interactionmentioning
confidence: 99%
“…Parents' capacities to attend to the adolescent’s thoughts, feelings and intentions have been described in terms of reflective function 34 , parental mindfulness 35 and meta-emotion philosophy 36 . This parental ability to attend to the adolescent’s experience in a non-reactive manner has been related to more positive parenting practices and less adolescent psychopathology 37, 38 .…”
Section: Parenting Practices That Facilitate Sensitive Attunementmentioning
confidence: 99%
“…According to Benbassat and Priel (2012) , who found a similar pattern between paternal RF and adolescents’ internalizing problems, high RF capacities would increase self-consciousness and the accuracy of self-perception, for better and for worse. While being able to more accurately reflect upon oneself, youths with good RF capacities would also be more conscious of their difficulties and of less desirable aspects of themselves, thus more prone to report emotional or behavioral difficulties ( Benbassat and Priel, 2012 ; Benbassat and Shulman, 2016 ). This hypothesis is coherent with our finding that RF-Self was associated with youths’ self-reported – but not parent-reported – internalizing symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, during this developmental period, the father–child relation is thought to be particularly significant, notably in the separation–individuation process ( Shulman and Seiffge-Krenke, 1997 ). One study found an intriguing positive association between fathers’ – but not mothers’ – RF and adolescents’ internalizing symptoms ( Benbassat and Priel, 2012 ; Benbassat and Shulman, 2016 ). The authors emphasized the impact of fathers’ outcomes in the psychological adjustment of their teenagers.…”
Section: Discussionmentioning
confidence: 99%